The College of Arts and Sciences Alumni Association (CASAA) food center an evaluation of its space and ventilation systems as perceived by the University of the Philippines (U.P.) students - Arreza, Emerson Balagtas; Cruz, Agerico V. (1992.)
The study involved an investigation of the present conditions in the CASAA's space and ventilation systems. It was found out that several problems became evident due to lack of design planning. After evaluating the data gathered during the study. It was deemed necessary that a new design plan and the improvement of the ventilation system be proposed. It is hoped that the study would improve the present conditions of CASAA food center to cater the needs of its customers.
Research paper (CTRA)--University of the Philippines Diliman.
Keywords: University of the Philippines. College of Arts and Sciences Alumni Association (CASAA)Foodservice Center; School canteen -- Philippines -- Quezon City -- Ventilation